2007
DOI: 10.1002/ejic.200700824
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 3,3‐Di‐tert‐butylthiirane trans‐1,2‐Dioxide and Its Reaction with a Platinum(0) Complex To Give a (Disulfenato)platinum(II) Complex: Regioselectivity of the Oxidation of a Related (Sulfenato–thiolato)platinum(II) Complex

Abstract: A three‐membered vic‐disulfoxide, 3,3‐di‐tert‐butyldithiirane trans‐1,2‐dioxide (8), was synthesized by oxidation of the corresponding dithiirane 1‐oxide 15 in high yield. Treatment of 8 and 15 with a platinum(0) complex, [(Ph3P)2Pt(η2‐C2H4)], yielded the (disulfenato)PtII complex 18 and the (sulfenato–thiolato)PtII complex 14, respectively, in high yields. Oxidation of the sulfenato–thiolato complex 14 with an acetone solution of dimethyldioxirane (DMD) took place at the sulfenato sulfur atom to yield the (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The best proof for the presence of dithiiranes as reactive intermediates is the interception with the Pt 0 (PPh 3 ) 2 complex fragment to form stable dithiolato complexes 5b,6e,6f,7. In contrast, the oxidative addition of the Pt 0 (PPh 3 ) 2 complex fragment into the sulfur–sulfur bond of 1,2,4‐trithiolanes does not allow the generation of thiosulfines by cycloreversion from this common type of precursor molecule 7a,8.…”
Section: Introductionmentioning
confidence: 99%
“…The best proof for the presence of dithiiranes as reactive intermediates is the interception with the Pt 0 (PPh 3 ) 2 complex fragment to form stable dithiolato complexes 5b,6e,6f,7. In contrast, the oxidative addition of the Pt 0 (PPh 3 ) 2 complex fragment into the sulfur–sulfur bond of 1,2,4‐trithiolanes does not allow the generation of thiosulfines by cycloreversion from this common type of precursor molecule 7a,8.…”
Section: Introductionmentioning
confidence: 99%
“…The Pt–S bonds are all of similar lengths; however, the Pt–S bonds in sulfinate complexes ( 12 , 17 , 26 – 29 ) are shorter that those in the other complexes. A search of the Cambridge Crystallographic Data Centre for structures containing the Pt-SO 2 R unit found only 23 reports of this substructure, of these 20 were cyclic (i.e., contained a chelating O 2 S^D unit, D = donor atom), meaning that only three unsupported Pt-SO 2 bonds have previously been characterized, and there were no Pt­(IV) sulfinates reported.…”
Section: Resultsmentioning
confidence: 99%
“…Almost 20 years ago, Ishii, Nakayama, and co‐workers reported the first synthesis of isolable, sterically crowded dithiiranes as well as their corresponding 1‐ S ‐oxides 5. 6 They demonstrated that these compounds were highly reactive towards [Pt 0 (PPh 3 ) 2 (η 2 ‐C 2 H 4 )] ( 5 ) and they characterized the isolated dithiolato complexes, as well as thiolato–sulfenato complexes, by X‐ray diffraction 6a. 7ac A similar reactivity was observed for naphtha‐[1,8 cd ][1,2]dithiols towards Pt 0 –olefin complexes 7d.…”
Section: Introductionmentioning
confidence: 88%